Clozapine prescription rates in Southeast Europe: A cross-sectional study - Russo, Manuela; Ignjatovic-Ristic, Dragana; Cohen, Dan; Arenliu, Aliriza; Bajraktarov, Stojan; Dzubur Kulenovic, Alma; Injac Stevovic, Lidija; Maric, Nadja; Novotni, Antoni; Jovanovic, Nikolina (Frontiers in Psychiatry, 2023)
International reports indicate that clozapine is under-prescribed. Yet, this has not been explored in Southeast European (SEE) countries. This cross-sectional study investigates clozapine prescription rates in a sample of 401 outpatients with psychosis from Bosnia and Herzegovina, Kosovo by United Nations resolution, North Macedonia, Montenegro and Serbia. Descriptive analysis was used to explore clozapine prescription rates; daily antipsychotic dosage was calculated and converted into olanzapine equivalents. Analysis of variance compared patients on clozapine vs those not on clozapine, and patients on clozapine monotherapy vs clozapine polytherapy regime. Results showed that clozapine was prescribed to 37.7% of patients (with cross-country variation: from 25% in North Macedonia to 43.8% in Montenegro), with average dose of 130.7 mg/daily. The majority of patients on clozapine (70.5%) were prescribed at least one more antipsychotic (the most frequent combination was with haloperidol). Our findings suggested that clozapine prescription rate in SEE outpatients is higher than in Western Europe. The average dose is significantly below the optimal therapeutic dosage recommended by clinical guidelines, and clozapine polytherapy was common. This might indicate that clozapine is prescribed mainly for its sedative effect rather than antipsychotic. We hope that this finding will be taken up by relevant stakeholders to address this non-evidence-based practice.